Participation in the Education and Training Sector - Colletta, Nat; Perkins, Gillian (World Bank, Washington, DC, 2012)
Operations in the education sector can be greatly improved by increasing the participation of government officials, education professionals, local communities, and the private sector. Such participation can increase the relevance and quality of education, improve ownership and build consensus, help to reach remote and disadvantage groups, mobilize additional resources, and build institutional capacity. Participatory operations involve risks and costs, however, and certain preconditions are necessary for success. These are: (a) early stakeholder analysis and involvement; (b) information sharing and dialogue among stakeholders; (c) flexibility in the funding, timing, and scale of projects; (d) institutional strengthening; and (e) appropriate systems of monitoring and evaluation, and mechanisms for ensuring accountability.